Takayasu Arteritis With Antiphosphatidylserine/Prothrombin Antibody-Positive Antiphospholipid Syndrome: Case Report and Literature Review. Issue 51 (December 2015) - Fukui, Shoichi; Hirota, Shogo; Iwamoto, Naoki; Karata, Hiroki; Kawakami, Atsushi
Abstract : Abstract: A relationship between Takayasu arteritis (TA) and positive antiphospholipid antibody states has been pointed out, but patients with TA complicated with antiphospholipid antibody syndrome (APS) are rare. Here we report the case of a 17-year-old Japanese man diagnosed with TA based on pulselessness of the left brachial artery, discrepancy of blood pressure between the upper extremities, and arterial wall thickening and narrowing of artery in contrast computed tomography. He was also diagnosed with provisional APS based on a pulmonary infarction without narrowing of the pulmonary artery and positive antiphosphatidylserine/prothrombin antibody. The patient also had concurrent Crohn's disease (CD) based on histopathological findings, which may have been associated with TA. We started high-dose corticosteroid therapy and anticoagulation therapy, and his symptoms including fever, dizziness, chest pain, and lower-right uncomfortable abdomen improved. We reviewed 9 cases of TA with APS including our patient by conducting a PubMed search. Based on past reports, we considered the relationship among TA, APS, and CD. Clinicians should bear in mind that many etiologies can exist in 1 patient, and differential diagnoses are essential.